Psychological stress and its relationship to social support among tenth and eleventh grade students during the selection of academic subjects in Sultanate of Oman - Al-Abri, Fatma Said Obaid; Maad, Ahmed (Journal of Educational and Psychological Sciences, 2023)
The current research aims to study the psychological pressures and their relationship with social support among tenth and eleventh-grade students in the Sultanate of Oman in the year 2023. The study focused on measuring the level of psychological pressures and their connection to social support during the course selection period. The descriptive method was employed, and the sample consisted of (773) male and female students from the tenth and eleventh grades. The sample was collected through a comprehensive census to ensure its representation of the study population. The Psychological Pressures Instrument developed by Al-Jabali (2006) was utilized, and the tool’s reliability and validity were calculated based on the Omani context. Additionally, the Social Support Instrument by Al-Senaidi (2021) was employed. The study found a correlation between psychological pressures and social support. It also revealed that the level of psychological pressures experienced by tenth and eleventh-grade students during the course selection phase was of moderate intensity with an arithmetic mean of (3.07). These pressures were most intense in the family and friends’ domains, with arithmetic means of (3.48 and 3.44) respectively. The study also indicated that the overall and sub-domain levels of social support (family and friends) were high, with arithmetic means of (3.70), (3.98), and (3.67) respectively. Furthermore, the study identified statistically significant differences in psychological pressures based on gender (males and females) and grade level, while no statistically significant differences were found in psychological pressures based on the type of education. Similarly, the study found statistically significant differences in the level of social support based on gender, grade level, and type of education.